Two new species of Kokeshia from China (Hemiptera: Heteroptera: Schizopteridae) - Rédei, Dávid; Ren, Shuzhi; Bu, Wenjun (Zootaxa, 2012)
Kokeshia xiei sp. nov. and K. zhengi sp. nov. (Hemiptera: Heteroptera: Dipsocoromorpha: Schizopteridae) are described from Hainan and Hubei Provinces of China, respectively.